Respuesta :
4(2n−1)−(2n+3)
=4(2n−1)+−1(2n+3)=4(2n−1)+−1(2n)+(−1)(3)=4(2n−1)+−2n+−3
=(4)(2n)+(4)(−1)+−2n+−3=8n+−4+−2n+−3
=8n+−4+−2n+−3=(8n+−2n)+(−4+−3)=6n+−7Answer:=6n−7
=4(2n−1)+−1(2n+3)=4(2n−1)+−1(2n)+(−1)(3)=4(2n−1)+−2n+−3
=(4)(2n)+(4)(−1)+−2n+−3=8n+−4+−2n+−3
=8n+−4+−2n+−3=(8n+−2n)+(−4+−3)=6n+−7Answer:=6n−7
4(2n-1)-(2n+3)
You can add a one to make it easier
4(2n-1)-1(2n+3)
Distribute the 4
2n(4)-1(4)-1(2n+3)
8n-4-1(2n+3)
Distribute the -1
8n-4+2n(-1)+3(-1)
8n-4-2n-3
Combine like terms
8n-2n-4-3
6n-7
Hope this helped!
You can add a one to make it easier
4(2n-1)-1(2n+3)
Distribute the 4
2n(4)-1(4)-1(2n+3)
8n-4-1(2n+3)
Distribute the -1
8n-4+2n(-1)+3(-1)
8n-4-2n-3
Combine like terms
8n-2n-4-3
6n-7
Hope this helped!